2011
DOI: 10.3758/s13421-011-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Classifying retrieval strategies as a function of working memory

Abstract: Strategy selection may help explain performance differences between individuals with high working memory capacity (HWMs) and low working memory capacity (LWMs) (Budd, Whitney, & Turley, (Memory & Cognition, 23, 735-748 1995); Cokely, Kelley, & Gilchrist, (Psychonomic Bulletin & Review, 13, 991-997 2006). We compared the independent and spontaneous strategy use of HWMs and LWMs during a category fluency (retrieval) task that required participants to retrieve animal names. HWMs were more successful at the fluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 23 publications
3
48
0
Order By: Relevance
“…Furthermore, examining the nature of the items retrieved suggested that high-and low-WMC individuals tended to retrieve in similar fashions, in that high-and low-WMC individuals retrieved similar proportions of items from each of the different categories. Finally, although high-and low-WMC individuals reported using very similar strategies overall, high-WMC individuals tended to rely more on their knowledge base to engage in general-to-specific searches than did low-WMC individuals, and low-WMC individuals were more likely than high-WMC individuals to engage in a random search in which items were passively retrieved (see also Schelble et al, 2012). Collectively, these results suggest that high-WMC individuals are more likely to use specific search strategies (as opposed to no strategy) than are low-WMC individuals, which helps in the self-generation of cues to search, resulting in more recalled items overall and more clusters of related items.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, examining the nature of the items retrieved suggested that high-and low-WMC individuals tended to retrieve in similar fashions, in that high-and low-WMC individuals retrieved similar proportions of items from each of the different categories. Finally, although high-and low-WMC individuals reported using very similar strategies overall, high-WMC individuals tended to rely more on their knowledge base to engage in general-to-specific searches than did low-WMC individuals, and low-WMC individuals were more likely than high-WMC individuals to engage in a random search in which items were passively retrieved (see also Schelble et al, 2012). Collectively, these results suggest that high-WMC individuals are more likely to use specific search strategies (as opposed to no strategy) than are low-WMC individuals, which helps in the self-generation of cues to search, resulting in more recalled items overall and more clusters of related items.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, this information was used to determine the different types of contexts (e.g., pets, farm animals, or zoo animals) that participants might use in recalling animals, as well as the relative proportions with which different contexts get searched. Finally, following the coding of each response, participants filled out a questionnaire regarding the various search strategies that they used to perform the fluency task (see also Schelble et al, 2012). Note that although prior work had investigated the relation between WMC and performance on this type of task, the prior work had not specifically examined the nature of the clusters generated, nor potential WMC differences in search strategies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low WM span individuals are less able to ignore distracters www.frontiersin.org (Unsworth, 2007), rely on context to recall items, and have fewer attentional resources (Conway and Engle, 1996;Kane et al, 2001;Unsworth and Spillers, 2010). Recent research has shown that high WM capacity participants adopted more efficient strategies in a category naming task compared to low WM capacity participants (Schelble et al, 2012). Importantly, however, when instructed to use the same strategy as the high WM capacity participants the low WM capacity participants performed just as well.…”
Section: Group Differences Modulate Tdcs Effect Sizementioning
confidence: 94%
“…Indeed, it is thought that the ability to keep memory and attention organized around relevant information drives the positive relationship between WMC and performance on a wide range of skills (Shipstead et al, 2014;Unsworth et al, 2014). Research demonstrates that individuals initially prefer, or are biased towards, using these complex strategies when they have the attentional resources to do so (DeCaro & Beilock, 2010;Schelble, Therriault, & Miller, 2012). For example, higher WMC individuals tend to look for patterns in random sequences (Wolford, Newman, Miller, & Wig, 2004), and continue to use complex, time-consuming algorithmic problem-solving approaches when simpler, more efficient strategies are available (Beilock & DeCaro, 2007;DeCaro, Thomas, & Beilock, 2008).…”
Section: Executive Attention and Insightmentioning
confidence: 99%